CHARACTERISTICS OF STUDENTS’ ABDUCTIVE REASONING IN SOLVING ALGEBRA PROBLEMS - Hidayah, Indriati Nurul; Sa'dijah, Cholis; Subanji, Subanji; Sudirman, Sudirman (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
When students solve an algebra problem, students try to deduce the facts in the problem. This step is imperative, students can draw conclusions from the facts and devise a plan to solve the problem. Drawing conclusions from facts is called reasoning. Some kinds of reasoning are deductive, inductive, and abductive. This article explores the characteristics of some types of abductive reasoning used by mathematics education students in problem-solving related to using facts on the problems. Fifty-eight students were asked to solve an algebra problem. It was found that the student’s solutions could be grouped into four types of abductive reasoning. From each group, one student was interviewed to have more details on the types. First, the creative conjectures type, the students can solve the problems and develop new ideas related to the problems; second, fact optimization type, the students make conjecture of the answer, then confirm it by deductive reasoning; third, factual error type, students use facts outside of the problems to solve it, but the facts are wrong; and fourth, mistaken fact type, the students assume the questionable thing as a given fact. Therefore, teachers should encourage the students to use creative conjectures and fact optimization when learning mathematics.